2016
DOI: 10.1177/1359105315597054
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of pain experiences in patients requiring hip and knee arthroplasty

Abstract: The aim of this study was to conduct an in-depth investigation of experiences with pain before knee and hip replacement surgery. A total of 20 patients were interviewed, and interpretative phenomenological analysis was used to identify themes. These were as follows: living with pain, pain conceptualised, pain treatments and healthcare system. Pre-surgical pain is very disabling and is viewed as biological. There was an associated loss of independence. Pharmaceutical management is used by all but not entirely e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Information provided to participants may have been different from what they reported, however, the use of ‘wear and tear’ and minimisation of OA by clinicians has been directly observed in consultations [25]. Although these findings are consistent with those found with other populations [13, 16, 17], caution is advised when applying these findings to other settings. The inclusion of consumers as part of the research team could have added insights to the analysis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Information provided to participants may have been different from what they reported, however, the use of ‘wear and tear’ and minimisation of OA by clinicians has been directly observed in consultations [25]. Although these findings are consistent with those found with other populations [13, 16, 17], caution is advised when applying these findings to other settings. The inclusion of consumers as part of the research team could have added insights to the analysis.…”
Section: Discussionmentioning
confidence: 51%
“…Beliefs about knee OA aetiology have been explored in a number of qualitative studies, indicating that many people consider OA to be an inevitable part of ageing that is influenced by wear and tear due to joint use and obesity [912]. There is a commonly held mechanical view of OA that focuses on loss of cartilage and bone abutting directly on bone [10, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The affected knee becomes locked up without warning (10,31) , increasing fall risks (31,32) . Pain originally from structural damage can interfere with daily activities, social interaction (22,23) , work, and sleep (22) . The current results also indicated that the women could not squat down to use a squat toilet-commonly used in Taiwan-or stand after squatting down.…”
Section: Before Decisionmentioning
confidence: 99%
“…Medical research and health services research has tended to be more quantitative in nature: less than one-third of the studies identified included a meta-analysis of patient education programs or were qualitative (Suhonen & Leino-Kilpi, 2006). Furthermore, available research often excludes the patient narrative and the experience of the patient (Leov et al, 2015). The ultimate conclusion of McDonald et al (2014) was that the use of preoperative education may be "a relatively low-risk" and "high reward" approach for those patients who are at increased risk of depression or anxiety or who maintain unrealistic expectations about surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing body of research on patient engagement, the process by which patients themselves make sense of education, such as preoperative joint replacement classes, is not addressed explicitly in the literature, especially for women. The voice of the patient, or the patient narrative, is notably absent in current research on TKA education outcomes (Leov, Barrett, Gallagher, & Swain, 2015). McDonald et al (2004) completed the first high-level meta-analysis that found preoperative education to have modest benefits for patients, but an updated meta-analysis in 2014 by the same authors introduced considerably more skepticism about the influence of education on clinical patient outcomes.…”
Section: Purpose Of the Studymentioning
confidence: 99%